DETERMINAN YANG MEMPENGARUHI PRILAKU PENGGUNAAN HYBRID LEARNING DI JURUSAN PARIWISATA POLITEKNIK NEGERI BALI: SUATU KERANGKA KONSEPTUAL - I Made Budiasa (Universitas Triatma Mulya, 2023)
The purpose of this study is to find out the determinants that influence the behavior of using Hybrid Learning (HL) in tourism learning at the Bali State Polytechnic Tourism Department. The research method used was a survey method using a questionnaire with Google Form to 70 lecturers using HL in tourism learning at the Bali State Polytechnic Tourism Department. Samples were lecturers who use HL at their teaching process. The consideration that the research was more focused on the acceptance of HL by lecturers. Primary data analysis was carried out quantitatively with the help of Smart PLS. The theoretical basis used is UTAUT (unified theory of acceptance and use of technology) with independent variables, namely in terms of technological characteristics including: performance expectancy, effort expectancy, social influence, facility conditions (facilitating conditions) and in terms of pedagogical characteristics it consists of authentic learning and authentic assessment, while the dependent variable is the use of HL (HL Usage/Adoption). The research found out that there is no limitations in using a particular theoretical concept that must be used in measuring an implementation or adoption of technology. In measuring the adoption and acceptance of a technology, it is necessary to consider in which field the technology is adopted so that it is necessary to think about an appropriate adaptation. Therefore, this concept needs to be considered as input in research on the adoption and acceptance of an LMS technology for further studies.